Prevalence of gingival enlargement secondary to calcium channel blockers in patients with cardiovascular diseases - Pedaballi, Priya (Medknow Publications & Media Pvt Ltd, 2012)
AIM: The purpose of the present study was to determine the prevalence and extent of gingival overgrowth in patients treated with calcium channel blockers for cardiovascular diseases. BACKGROUND: Calcium channel blockers are widely used in the treatment of hypertension, vasoplastic angina, and cardiacarrythmias. Gingival overgrowth resulting from the use of calcium channel blockers is of primary concern to dentists. The purpose of the present study is to determine the prevalence and extent of gingival overgrowth in patients treated with calcium channel blockers for various cardiovascular diseases, to assess their periodontal status and to correlate the factors like age, sex, duration, dosage, type of drugs that result in gingival overgrowth. MATERIALS AND METHODS: A cross-sectional study was done in cardiac patients treated with calcium channel blockers, visiting The Railway hospital, Perumbur, Chennai. Information regarding medical history, type, duration, dosage of medication were recorded and analyzed. The periodontal condition of the patients was assessed using the plaque index, gingival index, calculus index, papillary bleeding index, and extent of gingival overgrowth using appropriate indices. The data was later subjected to statistical analysis. RESULTS: In this study, a total of 213 cardiac patients (145 males and 68 females) who met the inclusion and exclusion criteria were screened. The patients were between 19 and 69 years. CONCLUSIONS: From the results of the present study it can be concluded that gingival overgrowth does occur with calcium channel blockers. Elderly males appeared to be more susceptible to the development of drug-induced gingival overgrowth, which was independent of dosage, duration of drug administered but the presence of local factors seemed to aggravate the same.